- #1

- 148

- 0

Big derivative, just want to make sure I am doing correct thing here.

a is the only changing dimension, r and l are constants

##\theta=\arccos\left(\frac{r^{2}+\left(r+l-a\right)^{2}-l^{2}}{2r\left(r+l-a\right)}\right)##

I want to differentiate ##\frac{d\theta}{da}##

So what I did was using

##\theta=\arccos a##

## cos\theta=a## differentiate this

## -sin\theta \frac{d\theta}{da}=1##

therefore with trig identities and a rearrange:

##\frac{d\theta}{da}=\frac{-1}{\sqrt{1-a^{2}}}##

where ##a = \left(\frac{r^{2}+\left(r+l-a\right)^{2}-l^{2}}{2r\left(r+l-a\right)}\right)##

So the derivative of theta with respect to a is

##\frac{d \theta}{da}=\frac{-a'} {\sqrt{1-a^2}}##

This involves the quotient rule, and I end up the expression below: I took out a factor of 4 top and bottom of the derivative of a, hence the 3/2 coefficient

##\frac{d\theta}{da}= \frac{ra^2 - (2r^2 - rl )a + (2r^{3}+3lr^{2}##

##+l^{2}r)}{ra^{3}-\frac{3}{2}r^{2}a^{2}+(2r^{3}+3lr^{2}+rl^{2})a-(r^{4}-2r^{3}l-r^{2}l^{2})}##

##\sqrt{1-(\frac{a^{2}-2a(r-l )+(2r^{2}+2rl)}{-2ra + 2r^{2} +2rl})##

Thanks

a is the only changing dimension, r and l are constants

##\theta=\arccos\left(\frac{r^{2}+\left(r+l-a\right)^{2}-l^{2}}{2r\left(r+l-a\right)}\right)##

I want to differentiate ##\frac{d\theta}{da}##

So what I did was using

##\theta=\arccos a##

## cos\theta=a## differentiate this

## -sin\theta \frac{d\theta}{da}=1##

therefore with trig identities and a rearrange:

##\frac{d\theta}{da}=\frac{-1}{\sqrt{1-a^{2}}}##

where ##a = \left(\frac{r^{2}+\left(r+l-a\right)^{2}-l^{2}}{2r\left(r+l-a\right)}\right)##

So the derivative of theta with respect to a is

##\frac{d \theta}{da}=\frac{-a'} {\sqrt{1-a^2}}##

This involves the quotient rule, and I end up the expression below: I took out a factor of 4 top and bottom of the derivative of a, hence the 3/2 coefficient

##\frac{d\theta}{da}= \frac{ra^2 - (2r^2 - rl )a + (2r^{3}+3lr^{2}##

##+l^{2}r)}{ra^{3}-\frac{3}{2}r^{2}a^{2}+(2r^{3}+3lr^{2}+rl^{2})a-(r^{4}-2r^{3}l-r^{2}l^{2})}##

##\sqrt{1-(\frac{a^{2}-2a(r-l )+(2r^{2}+2rl)}{-2ra + 2r^{2} +2rl})##

Thanks

Last edited by a moderator: